(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
The effects of boron (B) and vermicompost (VC) on growth and yield of Chilli (Capsicum annum L.) and nutrient accumulation in its fruits was examined. The highest plant height (22 cm), leaf number per plant (73), leaf area (502.53 cm2/plant), dry weight (22.27g/plant), fruit length (8.97cm), fruit number per plant (6), fruit yield (11.76 g/plant) were recorded in B0.5 kg/ha + VC5 ton/ha at harvest. The results of growth and yield of Chilli varied significantly (p<0.05) and increased with time. The total nutrient concentrations in the fruits were measured and varied significantly (p<0.05). The highest concentration of total P (0.028 %), K (2.50%), S (0.20 %), Cu (8.0 mg/kg), Fe (410 mg/kg) and Mn (0.80 mg/kg) in the fruit were observed in B0.5 kg/ha +VC5 ton/ha treatment and total N (0.41 %) and Zn (3.50 mg/kg) were found in B1.5 kg/ha + VC5 ton/ha treatment. The overall best growth, yield and nutrient accumulation in the fruits of Chilli was achieved in B0.5 kg/ha + VC5 t/ha treatment. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 31-36